A Facile Approach for Synthesizing Tetrabasic Lead Sulfate Derived from Recycled Lead-Acid Battery Paste and Its Electrochemical Performance. Issue 12 (1st January 2017) - Li, Mingyang; Yang, Jiakuan; Yu, Wenhao; Hu, Yuchen; Liang, Sha; Wang, Junxiong; Zhang, Wei; Zhang, Peiyuan; Liu, Jianwen; Wu, Xu; Hou, Huijie; Liu, Bingchuan; et al.
Abstract : The tetrabasic lead sulfate (4BS) additive, a high-value product, is synthesized directly from the starting materials of the spent lead paste in recycled lead-acid battery via a hydrometallurgical route. The synthesized 4BS products with two different particle size distributions are referred to as the Sintered 4BS and Ball-milled 4BS, with the mean diameter of 10, and 1 μm, respectively. The Ball-milled 4BS additive with smaller particle size can promote a denser and more integrated skeleton microstructure in the positive active materials (PAMs) after the formation process, compared with the Sintered 4BS additives. And C/20 and 1C initial discharge capacities of testing batteries with the Ball-milled 4BS additives are better than those with the Sintered 4BS additives. Moreover, both synthesized 4BS additives can improve the capacity retention characteristics of the testing batteries during charge/discharge cycles. The Ball-milled 4BS additive at a dosage of 0.5–1 wt% in PAMs is proposed. The feasibility of recovery of valuable 4BS product directly from the spent lead paste is proved, which paves a green recycling route for hazardous wastes comprising lead.